KEBIJAKAN STRUKTUR MODAL DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN Pendekatan Persamaan Simultan Pada Perusahaan-Perusahaan LQ45 Yang Terdaftar di Bursa Efek Indonesia - Stevany Febreany, SE., M.Ak. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2017)
This research is to examine the effect and the correlation of capital structure policy on firm value which includes the effect of profitability, asset structure and growth opportunity as factors affecting capital structure and corporate value. The data used are historical data and financial data such as financial statements of LQ45 companies in Indonesian Stock Exchange (BEI).This study uses the entire population of LQ45 companies listed in Indonesia Stock Exchange period 2010 to 2013. Of the population obtained a sample of 30 companies using purposive sampling method. Researches used multiple linear regression to simultaneously test, the relationship between independent variable vs dependent variable, and to test the relationship between the two dependent variable. Researches used 2SLS (two stage least square) with significance level of 5% alpha to test the relationship between the two dependent variables.Results of this study partially demonstrated that the relationship of mutual influence/simultaneous interdependence between capital structure and firm value is significantly positive.